Bone marrow stem cells in experimental stroke - Kocsis, Jeffery D.; Honmou, Osamu (Progress in Brain Research, 2012)
Adult bone marrow-derived mesenchymal stem cells (MSCs) have a remarkable spectrum of functional properties. Transplantation of MSCs improves clinical outcome in animal models of cerebral ischemia, and traumatic brain and spinal cord injury, via mechanisms that may include induction of axonal sprouting and remyelination, protection of injured neurons, neovascularization, and, potentially, replacement of damaged cells. Beneficial therapeutic effects have been reported in experimental models of stroke following intravenous delivery of MSCs. Initial clinical studies using intravenously delivered MSCs have been initiated in human subjects with stroke. This chapter reviews multiple beneficial effects of MSCs in experimental stroke models, describes initial human clinical studies on intravenous MSC delivery in stroke, and provides a perspective on further experimental and clinical studies of MSCs.